(3GdadSaI heOGNd GdYed s - (3SdeGf(B, (3RjOGfs ((3YeGf(B:s (3OGQ GdefGgL ddfTQ hGdJhRjY(B,s, 2023)
(3agPG gh GdLRA GdKGfj ef cJGH (B( (3EOGQI GdLhOI GdTGedI(B.. (3GdeOGNd hadSaI GdYed (B) (3dnfSJced ajg hfhqVM CgejI gPg GdQcjRI GdJGQjNjI hGdeYGUQI GdegeI, hGdhXjaI GdYXei ef hXGFa GdEOGQI heSFhdjGJ GdbjGOGJ GdYdjG hGdOfjG aj GdTQcGJ hGdeDSSGJ GdEfJGLjI hGdNOejI , hCgejI GdOhQ GdMGSe GdPj JdYHg aj eSGQGJ heaGUd JMSjf GdYedjGJ Ydi GNJdGa CfhGYgG hCfeGWgG , haj OYe hJYRjR efGgL GdHMK hGdJWhjQ hGdGdJRGe HGdehGUaGJ hGdebGjjS GdhWfjI hGdOhdjI hJWHjbgG Ydi GdYedjGJ GdEfJGLjI hCKfGA JbOje GdNOeGJ , heG HYO Pdc (B.(3JhRY GdLRnA GdKGfj Ydi YTQI aUhd, eY bGFeI HGdeUWdMGJ (B( (3GdYQHjI hGdGfLdjRjI (B) (3GdNGUI HEOGQI GdLhOI GdTGedI heG jQJHW HgG , HGdEVGaI Edi GdeQGLY hGdeUGOQ GdJj faYJ GdOQGSI , MGhdfG aj gPg GdaUhd GSJceGd GdELGHI Ydi GdJSGDdGJ GdeWQhMI aj GdLRA GdChd HTCf CgejI EOGQI GdLhOI GdTGedI aj GdMjGI GdeYGUQI, eKdeG cGfJ HPj VQhQI dOi GdCLjGd GdeGVjI ef Hfj GdHTQ, hHNGUI YfO GdYQGbjjf hGdjefjjf hGdeUQjjf hZjQge ef YHGO Gddg GdNGdpb JHGQnc hJnYGdi, YdGhkI Ydi GgJeGe GdESdGe GdYXje HQhM GdYed GdLeGYj hHYedjGJ GdEJbGf hGdObI hGdENdGU hGdhaGA hGdUOb aj GdYed , hGdhdhL MjfPGc aj CYeGb hOhGNd GdEfSGf GdeDef , hGdGJUGd GdYVhj HeaGUd EOGQI GdLhOI GdTGedI hbhGfjfgG hCfXeJgG heYWjGJgG GdJj dG JJMbb ef Ohf JYGhf GdeSJhjGJ cGaI, HOAkG ef GdbjGOGJ GdCeGejI GdYdjG MJi GdTYjQGJ GdUZjQI aj GdMjGI , Vef MdbGJ GdEfJGL haYGdjGJ JbOje GdNOeI, hCSGdjH GdYed eaGUdg (B.s
(3GdeQGLY U(B.279 (3bGFeI GdeUWdMGJ U(B.273s
Keywords: (3EOGQI GdLhOI GdTGedIs